"TRANSMISSIBLE DRUG RESISTANCE AMONG SALMONELLA TYPHIMURIUM AND ENTEROPATHOGENIC E. COLI IN IRAN " - S.Mohadjer; Sh.Hakimi; M.Mohamadi (Tehran University of Medical Sciences, 1978)
The antimicrobial susceptibility of 118 S.typhimurium and 84 enteropathogenic E. coli isolated from human gastero-enteritis cases were examined. More than 25 different resistant patterns could be identified. Most of the strains of S. typhimurium possessed R-factors bearing resistance to ampicillin, chloromycetin, kanamycin, streptomycin, sulfonamide and tetracycline. More than 50% and more than 6% were resistant to furazolidon and nalidixic acid respectively. But they all were sensitive to gentamicin. The majority of S. typhimurium strains were harboring resistant determinats but not the RTF plasmid. Almost all the resistances could be mobilized using fi-, I-like and fi+, F-like transfer factor except for K-resistance. The E.coli strains behaved differently, that is: the majority of the strains showed resistances to chloromycetin, streptomycin, sulfomamide and tetramycine. They were all sensitive to gentamicin, furazoldon and nalidixic acid. And also the majority of the strains were harbouring both, resistant determinates and RTF plasmid. Among the non-rtansferable and non-mobilizable resistances, streptomycin-sulfonamide determinants were the most common ones.